Comparison Study of Performance Evaluation of Sultan Abdurahman-Sulawesi Unsignalized Intersection in Pontianak using MKJI 1997, PKJI 2023 and PTV VISSIM - Iftitah, Nadhifa Nur; Kadarini, S. Nurlaily; Azwansyah, Heri (Fakultas Teknik Universitas Tanjungpura, 2025)
The increasing traffic congestion in Pontianak City, primarily driven by population growth and rising mobility, poses a significant challenge for urban transportation management. One of the critical congestion points is the unsignalized triangular intersection at Jalan Sultan Abdurrahman and Jalan Sulawesi, located near public facilities. This study aims to evaluate the performance of this intersection under existing conditions and projected conditions for the year 2029, using the analytical approaches of MKJI 1997, PKJI 2023, and PTV VISSIM software. Primary data were collected through field surveys, while secondary data were obtained from technical documents and official sources, then processed using Microsoft Excel and presented in tables and graphs. The analysis results indicate that the PKJI 2023 method represents current traffic conditions more than MKJI 1997, as its outcomes align more closely with the PTV VISSIM simulation results. Furthermore, the 2029 projection analysis reveals a significant increase in traffic delays, with the Level of Service (LOS) declining from A to C. Among eight evaluated alternative treatments, widening the main road lanes to 5 meters in each direction proved to be the most effective solution, reducing delays to 12,13 seconds per vehicle and improving the LOS to category B.